Identifying Agricultural Factor Productivity from Micro-data: A Review of Approaches with an Application to EU Countries - Martin Petrick; Mathias Kloss (German Journal of Agricultural Economics (GJAE), 2018)
We examine the plausibility of four established and innovative identification strategies for agricultural production functions using farm-level panel datasets from five EU countries. Newly suggested proxy and dynamic panel approaches provide attractive conceptual improvements over received Within and duality models. Even so, empirical implementation of such advancements does not always live up to
Keywords: 330